Tacirin ücret ve faiz isteme hakkı - Atmaca, Abdulkadir Cenap (My University, 2000)
TEZ ÖZETİ Tezin konusu, tacirin ücret ve faiz isteme hakkıdır. Bu hak, tacire kanun tarafından tanınmıştır. Birinci bölümde tacir olmanın şartları, kimlere tacir denildiği, tacir sıfatının kazanılması ve kaybedilmesi anı gibi konular ele alınmıştır. Bu yapılırken gerçek ve tüzel kişiler ayrı ayrı incelenmiş; bunun yanında tacir sayılmamasına rağmen tacir gibi sorumlu olan zümreye ve tüzel kişiliği bulunmamasına karşın tacir sıfatı kanun tarafından tanınmış olan donatma iştirakine de değinilmiştir. İkinci bölümde tacirin ücret isteme hakkı incelenmiştir. Bu inceleme TTK.m.22 kapsamı içinde kalarak yapılmıştır. Zira tacirin ücret isteme hakkı bu maddede düzenlenmiştir. Genel kural niteliğindeki bu hüküm tüm tacirler için geçerlidir. Evvela tacirin ücret isteyebilmesi için gerekli olan şartlar sayılmıştır. Daha sonra ücret isteyebileceği durumlara değinilmiştir. Özellikle vekaletsiz iş görme durumunu incelerken, önce borçlar hukukundaki düzenlemeye yer verilmiş, daha sonra ticari işlerdeki durumdan bahsedilmiştir. Ardından tacirin talep edebileceği ücret miktarı ele alınmıştır. Bunun için karşı tarafın tacir olup olmaması ya da tacirle aralarında bir sözleşme bulunup bulunmadığı kriterlerine başvurulmuştur. En sonunda da ücretin istenebileceği zaman dilimi ve ödeme yeri hakkında açıklamalar yapılmıştır. Üçüncü bölümde ise, tacirin tacir sıfatına sahip olması nedeniyle ve kanun hükmü gereğince almaya hakkı bulunan faiz konusu ele alınmıştır. Bu incelemenin sınırlarını yine TTK.m.22 oluşturmaktadır. Dolayısıyla faiz konusu tüm ayrıntılarıyla irdelenmemiştir. Madde kapsamında olmayan temerrüt faizi gibi konulara girilmemeye çalışılmıştır. Önce faizin tanımı ve çeşitlerine kısaca değinilmiş, ardından tacirin faiz isteyebileceği durumlar sayılmıştır. Daha sonra tacirin isteyebileceği faizin niteliği de dikkate alınarak faiz oranı, işlemeye başlayacağı zaman ve zamanaşımı konuları ele alınmıştır. Sonuç bölümünde ise konuyla ilgili genel bir değerlendirme yapılmıştır.

This thesis analyses merchant's legal right to claim charge and interest. The study is composed of three chapters along with Conclusion and Bibliography. The first chapter covers the concept of merchant. This chapter clarifies such subjects as conditions to be attributed status of merchant, person who may be considered to be a merchant and the time when status of merchant is gained and lost. Both legal and natural persons are analyzed separately from each other, more over, the group who are not themselves merchant held liable as if they were merchant and, lastly, maritime joint-adventure that has no legal personality but attributed status of merchant is analyzed. The second chapter analyses merchant's right to claim charge. This analysis is made within the limits of Turkish Commercial Code Article 22, which is the article on the subject. The article has the characteristic of a general rule, therefore, it is applicable to all merchants. The article, first, lays down pre-conditions to claim charge, then comes, situations in which s/ he can claim charge. Especially in the analysis of negotiorum gesti provisions of Obligation Law was clarified before analyzing commercial deals. Afterwards, amount of the charge that a merchant may claim is clarified. Within the analysis, the criterion if the other party of the agreement is a merchant is employed along with the criterion whether the parties are in relation of an agreement or not. At the end of the chapter, the time period when and the place where the charge may be claimed is explained. The third chapter is devoted to the subject of right to claim interest that a merchant has as a result of both status of merchant and provision of Article 22 of Turkish Commercial Code. This analysis is limited to the provision of the said Article 22. Therefore, every aspects of subject of interest are not illustrated, the subjects that are not within the scope of the article, such as moratory interest, are not included into the analysis. First of all definition and types of interest is clarified in sum, after that situations in which a merchant may claim interest are indicated. Later on, subjects of interest rate, the time when the right to claim starts and prescription are analyzed in the light of the characteristic of the interest that a merchant may claim. Conclusion is the final part of the study where general comments on the subject are given-place.
Keywords: Ticaret hukuku; Tüccarlar